MOIM: a novel design of cryptographic hash function - Alahmad, Mohammad; Alshaikhli, Imad Fakhri Taha (International Association for Medical Engineering And Management Education (IAEME), 2013)
A hash function usually has two main components: a compression function or permutation function and mode of operation. In this paper, we propose a new concrete novel design of a permutation based hash functions called MOIM. MOIM is based on concatenating two parallel fast wide pipe constructions as a mode of operation designed by Nandi and Paul, and presented at Indocrypt 2010 where the size of the internal state is significantly larger than the size of the output. And the permutations functions used in MOIM are inspired from the SHA-3 finalist Grøstl hash function which is originally inspired from Rijndael design (AES). As a consequence there is a very strong confusion and diffusion in MOIM. Also, we show that MOIM resists all the generic attacks and Joux attack in two defense security levels.